Two-Dimensional Particle Assembly Based on the Synchronized Evolution of Centrosymmetric Off-Axis Acoustic Vortexes - Ding, Ning; Guo, Gepu; Tu, Juan; Zhang, Dong; Ma, Qingyu (Engineering (Beijing, China), 2025)
Acoustic-vortex (AV) tweezers ensure stable particle trapping at a zero-pressure center, while particle assembly between two vortex cores is still prevented by the high-potential barrier. Although a one-dimensional low-pressure attractive path of particle assembly can be constructed by the interference between two independent cylindrical Bessel beams, it remains challenging to create two-dimensional (2D) neighboring vortexes using a source array in practical applications. In this paper, a three-step phase-reversal strategy of 2D particle assembly based on the synchronized evolution of a centrosymmetric array of M off-axis acoustic vortexes (OA-AVs) with a preset radial offset is proposed based on a ring array of planar sources. By introducing initial vortex phase differences of −2π/M and +2π/M to the vortex array, low-pressure patterns of an M-sided regular polygon and M-branched star are formed by connecting the vortex cores and the field center before and after the tangent state of adjacent OA-AVs. Center-oriented particle assembly is finally realized by a central AV constructed by coincident in-phase OA-AVs. The capability of particle manipulation in the lateral and radial directions is demonstrated by low-pressure patterns with acoustic radiation forces pointing to the field center during a synchronized central approach. The field evolution is certified by experimental field measurements for OA-AVs with different vortex numbers, initial vortex phase differences, and radial offsets using a ring array of 16 planar sources. The feasibility of particle assembly in two dimensions is also verified by the accurate manipulation of four particles using the low-pressure patterns of a four-sided polygon, a four-branched star, and a central AV in experiments. The three-step strategy paves a new way for 2D particle assembly based on the synchronized evolution of centrosymmetric OA-AVs using a simplified single-sided source array, exhibiting excellent potential for the precise navigation and manipulation of cells and particles in biomedical applications.